Integrating AI Technology to Optimize Learning for SD Muhammadiyah Kebumen - Djoko Sutrisno; Ani Susanti; Hermanto (Mutiara Intelektual Indonesia Press, 2024)
Artificial intelligence has the potential to revolutionize education by enhancing teaching and learning experiences. By integrating AI technology, SD Muhammadiyah Kebumen can optimize its teaching methods and improve the overall learning outcomes for students. However, successfully integrating AI technology into education requires addressing specific challenges and considerations. These challenges include the profit-oriented nature of current AI applications in education, the lack of pedagogical knowledge among AI developers, and the need for teachers' input and collaboration in the development process. This paper explores the potential of integrating AI technology to optimize SD Muhammadiyah Kebumen's learning. The method of this research is a mix of methods, combining both quantitative and qualitative approaches. The quantitative approach will involve analyzing data on the current teaching methods and learning outcomes of SD Muhammadiyah Kebumen. The qualitative approach will include conducting interviews and surveys to gather insights and perceptions from teachers regarding the use and effectiveness of AI technology in their classrooms. The results show that integrating AI technology in teaching can improve the quality and effectiveness of instruction, enhance student engagement and personalized learning experiences, and provide teachers with valuable insights and data to inform their teaching practices. The score is approximately 3.78, suggesting a somewhat positive attitude towards AI among the respondents. Current use of technological tools: This category scored the highest, with a mean score of around 4.12, indicating that the current use of technological tools is favorable among the participants. Perceived benefits of AI integration include improved student outcomes, increased efficiency in teaching, personalized learning experiences, enhanced engagement, and access to valuable data for informed decision-making. The study found that integrating AI technology in teaching can potentially optimize learning for SD Muhammadiyah Kebumen